Traditional knowledge of small farmers in the hydrographic bowl of rio Duas Bocas, state of Espírito Santo: An Ethnoclimatologic Approach - Dias Nunes Kiffer, Julhia; Antunes Zappes, Camilah; Marchioro, Eberval (Geografares, 2020)
The observation of the signs of nature throughout human existence has benefited the construction of empirical knowledge about the climate. The aim of this study is to describe social aspects, to characterize the local knowledge related on meteorological forecast indicators from the knowledge of small farmers living in the surroundings of the Duas Bocas Biological Reserve, Cariacica county, state of Espírito Santo (ES), southeastern Brazil, located in the Two Bocas River Hydrographic Basin. Fifty semi structured ethnographic interviews were carried out, besides the application of the participant and direct observations; and used a field diary. Local farmers are mostly males (n = 41), have been farming in the region for at least 40 years, and have a low level of education with incomplete primary education. The main cultivation in the region are banana, coffee and manioc. Summer is the season with the highest agricultural production due to high temperatures and high rainfall. Most local farmers (n = 41; 82%) trust on the ethnoclimatological prediction derived from traditional knowledge. Atmospheric dynamics, fauna behavior and celestial bodies were the main indicators of rain. Ethnoclimatological knowledge is important in the maintenance of the agricultural practice in the studied region, since the success of the harvest depends on this local knowledge.
Keywords: Traditional knowledge; agriculture; weather indicators